(untitled) (Quinto Sol, 2019)
The article reconstructs the way the Buenos Aires police used to its advantage the increase in crime news in the Buenos Aires press in the first years of the twentieth century. This news, which often presented police action in order to criticise it, also provided the possibility for the police to make a good impression. To research this productive area of contact for the police, the article focuses on the news coverage of anarchist attacks frustrated by the Comisaría de Investigaciones (Bureau of Investigations), the division responsible for monitoring anarchists in Buenos Aires. This focus is justified because anarchism was a powerful local social movement, and due to its use bombs and assassinations of major international political figures it was firmly installed in the city press as an issue of enormous journalistic output. Hence the article argues that anarchism in the press provided the possibility for the police to dignify their work, reward officers, and demonstrate their competence in anticipating terrorist attacks in the city.